Reinforced concrete beams strengthened with externally bonded natural flax FRP plates. (15th April 2016) - Huang, Liang; Yan, Bin; Yan, Libo; Xu, Qi; Tan, Haozhi; Kasal, Bohumil
Abstract: This paper reports an investigation on the use of natural flax fabric reinforced polymer (FFRP) composite plates as external strengthening material of reinforced concrete (RC) beams. The flexural behaviour of 2 m-long RC beams with and without FFRP plates are evaluated under four-point bending. The test variables include FFRP thickness (4 and 6 layer), the amount of internal steel reinforcement ratio (0.223% and 0.503%) and a pre-cracking of RC beams (i.e. by applying 80% yielding load of the control RC beam before the bond of FFRP plates to the RC beams). The test results indicated that FFRP plates enhance the ultimate load, deflection and ductility of the beams significantly. The increase in load and ductility is more effective for RC beams with a lower steel ratio. The strengthened beams show a similar failure mode, i.e. steel yielding and then rupture of the FFRP plate. Pre-cracking of the RC beams has no obvious effect on the ultimate load and energy absorption capacity of the FFRP strengthened beams, indicating that FFRP will be effectively to retrofit damaged RC beams (e.g. after earthquake-attack). In addition, the experimental results are compared with the predictions based on the equations given in ACI 440.2R-08 for RC beams strengthened with synthetic FRP composites. This study therefore concludes that natural flax FRP composite is an effective external reinforcement material for strengthening deficiently-designed and/or damaged RC members after earthquakes.